CONTACT DERMATITIS AMONG CONSTRUCTION WORKERS - Ida Ayu Diah Purnama Sari; Luh Mas Rusyati; I Gusti Ketut Darmada (E-Jurnal Medika Udayana, 2013)
Contact dermatitis is a form of skin inflammation with spongiosis or intercellular edema of the epidermis due to the interaction of irritants and allergens. While occupational contact dermatitis is an inflammation of the skin due to exposure to irritants or allergens in the workplace. One of the jobs that have a high risk of the disease are construction workers. Although the disease is rarely-threatening but can cause high morbidity and suffering for workers, so it can affect the economy and quality of life of patients.